Analysis of ancient grammatical discourse in light of Robin Lacoff’s literary rules - Ahmed Hashim, Prof. Hussam; Naeem Shanawa, Prof. Dr. Khaled (Basra studies journal, 2026)
This research aims to examine ancient grammatical discourse in light of Lakoff’s politeness theory, revealing the extent to which grammarians adhered to the principles of politeness in their scholarly dialogues and the areas of deviation from them. The study relied on the analysis of selected grammatical texts to identify the features of the polite principle of modesty, choice, and courtesy, as formulated by Lakoff. The results revealed that grammatical discourse was not merely a linguistic debate, but rather a communicative space characterized by the presence of rules of politeness that preserved the faces of the interlocutors and framed the dialogue with a degree of respect, despite the occasional sharpness or conflict that reached the point of threatening or shedding one’s face. This reading confirms that Lakoff’s theory serves as a framework for understanding the pragmatic depth in the Arabic grammatical heritage, linking the approaches of ancient dialogue with contemporary pragmatic tools. It reveals that traditional scholarly discourse was not immune to the principles of human communication.